Lithuanian itinerant gangs in the Netherlands - SIEGEL, DINA (Kriminologijos studijos, 2014)
Since the end of the 1990s, the police in the Netherlands has regularly reported on the criminal activities of Lithuanian itinerant groups as part of the mobile banditry phenomenon. According to the reports, these groups commit crimes against property, they are highly professional and well-organized. In particular, they are involved in vehicle, shop, and cargo theft and burglaries. The present article is based on the research conducted in 2013 and aims to provide explanations and analyses of the historical, socio-economic, and political backgrounds of the ‘itinerant criminal gangs’ phenomenon. The focus is on the gangs from Lithuania. The analysis is done from different perspectives: lessons from the past (historical analysis of banditry); the rise of organized crime as a consequence of the collapse of the socialist economy (economic analysis of new markets and clients); the context of globalization, and particularly enlargement of the European Union, the irresistible attraction of the West and the gap between the wealthy West (the Netherlands) and the poor East (Lithuania) (cultural criminological analysis of the push and pull factors). The precise and detailed description of the modus operandi, structure, leadership, and targets of the Lithuanian groups are illustrated by various quotes of the ‘intern’ respondents, from police and justice experts in specific areas in Lithuania and the Netherlands to Lithuanian detainees in Dutch prisons. Where are the stolen goods, are they brought back to the Lithuanian market, or further on to the former Soviet republic, or perhaps they are sold to the local Dutch merchants in the local settings? How the contacts between Lithuanian and Dutch (or Afghan, Russian, etc.) criminals are created? These questions are answered on the basis of numerous interviews, observations and comparative literature analysis.The last part of the article focuses on the questions how to tackle and combat this relatively new form of organized crime and what are the responsibilities of different institutions and organizations in this context (in the EU, in the Netherlands, and in Lithuania).
Keywords: Organized crime; mobile banditry; Lithuanian criminal gangs; car-theft